The anatomy of dependence - Doi, Takeo (Kodansha international Ltd., 1973)
A classic study of the Japanese psyche, a starting point for a true understanding Japanese behavior....The discovery that a major concept of human feeling -- easily expressed in everyday Japanese -- totally resisted translation into a Western language led Dr. Takeo Doi to explore and define an area of the psyche which has previously received little attention. The resulting essay, The Anatomy of Dependence, is one of the most penetrating analyses of the Japanese mind ever written, as well as an important original contribution to psychology which transcends the boundaries of cultures and nations.